Cancer Immunotherapy by Targeting IDO1/TDO and Their Downstream Effectors - Platten, Michael; von Knebel Doeberitz, Nikolaus; Oezen, Iris; Wick, Wolfgang; Ochs, Katharina (Frontiers in Immunology, 2015)
The tryptophan to kynurenine metabolic pathway is now firmly established as a key regulator of innate and adaptive immunity. A plethora of preclinical models suggests that this immune tolerance pathway - driven by the key and rate-limiting enzymes indoleamine-2,3-dioxygenase and tryptophan-2,3-dioxygenase - is active in cancer immunity, autoimmunity, infection, transplant rejection and allergy. Drugs targeting this pathway, specifically indoleamine-2,3-dioxygenase, are already in clinical trials with the aim at reverting cancer-induced immunosuppression. In the past years there has been an increase in our understanding of the regulation and downstream mediators of tryptophan metabolism, such as the aryl hydrocarbon receptor as a receptor for kynurenine and kynurenic acid. This more detailed understanding will expand our opportunities to interfere with the pathway therapeutically on multiple levels. Here we discuss the perspective of targeting tryptophan metabolism at these different levels based on reviewing recent insight into the regulation of tryptophan metabolism and its downstream effectors.